Board Governance, Risk Governance And Bank Performance: The Moderating Role Of Competitive Intensity On Banks In Kuwaitfactors Influencing The Roles Of Environmental Ngos In The Bargaining Of P-xylene And Water Issues In Yunnan, China - Hayati, Mohammad A M A B H (2023)
Corporate and risk governance topics have gotten attention in the past years due to the impact of the successive financial crises. The focus of central banks and legislative institutions on these issues has taken a large part in order to support economies and increase investor confidence. This study focuses on studying the impact of new corporate governance regulations that was issued by the Central Bank of Kuwait (CBK) in year 2012 on the accounting-based performance, measured by return on assets (ROA) and return on equity (ROE) and market based-performance, measured by Tobin’s Q and stock price movement. The sample selection includes 10 listed banks in the Kuwait stock exchange (KSE) covering the period from 2013 until 2019. The study selects three board governance variables namely board of directors’size, board of directors’ independence, and board of directors’ yearly meetings. The study as well chooses chief risk officer (CRO) presence, risk management committee size and yearly meetings as risk governance variables while bank size and bank leverage are used as control variables. The study highlights the importance of competitive intensity in the banking sector, which scarce research has been done on corporate governance previously, measured by bank concentration ratio (BCR) as a moderating variable that could impact the relationship. the study applies panel data regression analysis such as fixed effect model (FEM), random effect model (REM), and ordinary least square (OLS) method to examine the relationships.